Neokantismo, valores e razão discursiva: aproximações da metodologia jurídica com a axiologia política kantiana - Lima, Newton de Oliveira (Revista Ágora Filosófica, 2016)
The neokantianism as a philosophical school of thought of Law developed as legal knowledge method that searched for a phenomenological intuition prescribe legal values . The linguistic- pragmatic turn in philosophy in the mid- twentieth century led to the replacement of the legal neokantianism by a linguistic methodology on the Law within a justifying discourse procedure of human rights as core values (liberty, equality, common good) and a procedural rationality who returns to Kant as a defense of State of Law. We will seek to map the discourse and Kantian justification of Law from the thought of Ricardo Terra and its approach to legal values as linguistic objects, paving the way for a new legal methodology based on constructed values arguably and according to the principles of kantian reason.